The psychological implications of returning to sport post-isolation - Dithurbide, L. (Sport Information Resource Centre SIRC, 2020)
As public health restrictions begin to lift across the country, the return to some form of sport participation will require adjustment and adaptation. As athletes return to sport, the virus is still present, and so is the uncertainty. The cancellation of sport events and the imposition of stay-at-home and physical distancing protocols over the last several months have caused many athletes to experience a loss of control, even a loss of their sense of identity (Koninckx & Teneau, 2010). These feelings of loss may continue long after returning to training.